(untitled) (GYMNASIUM, 2009)
Talking about mental stability of course focuses on a positive state of mind thus resulting in a good performance. The performance of any athlete in this status is very good, sometimes remarkably beyond their regular capacity. The most recent researches do lead to the level of self value of the respective athlete as the most decisive factor of the stabilization of performance. The crucial point is to find certain drills and configurations of tasks that will give a good chance for the athlete to be successful in showing competence.